2018
DOI: 10.1002/app.46572
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the clay sensitivity and cement hydration process of modified HPEG‐type polycarboxylate superplasticizers

Abstract: In this work, three kinds of HPEG-type polycarboxylate superplasticizers (PCs) were synthesized with three kinds of typical functional monomers: [diallyl dimethyl ammonium chloride (DMDAAC), 2-hydroxyethyl methacrylate (HEMA), and 2-(dimethylamino) ethyl methacrylate (DMAM), respectively. The effects of montmorillonite clay on the fluidity of cement/PC pastes were investigated. It was found that the fluidity was negatively affected by the clays in the order: DMAM-PC < HEMA-PC < conventional PC (CPC) < DMDAAC-P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…The polyether macromonomers used in the production of PCE mainly include methoxy‐PEG, allyl‐PEG, methallyl‐PEG (HPEG), and isoprenol‐PEG (IPEG) macromonomers. According to the usage statistics, HPEG and IPEG are still the most commonly used macromonomers, when such two macromonomers be used to synthesize PCE, a heating reaction process is usually employed (the reaction temperature is 30–60 °C, even 80 °C sometimes), and the production cycle is about 4–5 h . By analyzing the structure of these two commonly used macromonomers, it can be found that they are all the same type of vinyl alcohol‐based macromonomers because their starting agents are both vinyl alcohol.…”
Section: Introductionmentioning
confidence: 99%
“…The polyether macromonomers used in the production of PCE mainly include methoxy‐PEG, allyl‐PEG, methallyl‐PEG (HPEG), and isoprenol‐PEG (IPEG) macromonomers. According to the usage statistics, HPEG and IPEG are still the most commonly used macromonomers, when such two macromonomers be used to synthesize PCE, a heating reaction process is usually employed (the reaction temperature is 30–60 °C, even 80 °C sometimes), and the production cycle is about 4–5 h . By analyzing the structure of these two commonly used macromonomers, it can be found that they are all the same type of vinyl alcohol‐based macromonomers because their starting agents are both vinyl alcohol.…”
Section: Introductionmentioning
confidence: 99%
“…As shown in Figure 5, while the crosslinker was broken, the crosslinked struc-ture can be hydrolyzed into comb-like molecular fragments. Thus, a secondary dispersion of the hydrolytic fragments was carried out in the suspension, which improved the dispersion retention capacity of the cement pastes [24]. However, the exact mechanism of the dispersion of crosslinked-PC in the cementitious system requires further investigation.…”
Section: Fluidity and Time-dependent Fluidity Lossmentioning
confidence: 99%
“…Low temperature cement [27][28][29] can reduce the structure temperature and improve the crack resistance of the concrete structure. Additives [30][31][32][33][34] can also effectively reduce the temperature rise of cement hydration heat. e arrangement of cold water pipes is a very effective method to reduce the heat of hydration [35].…”
Section: Introductionmentioning
confidence: 99%